Effect of Thawing Process on the Quality of Chicken Thigh Meat - Anggita Reizda Siman; Winiati Pudji Rahayu; Uswatun Hasanah (The University of Lampung, 2026)
Frozen meat handling, especially during the thawing stage, can affect meat quality and influence the final product. This study aimed to evaluate the effects of thawing method and duration on the quality of frozen and steamed chicken thigh meat. The experiment was arranged in a completely randomized design with two replications. The thawing methods included room temperature (4, 5, 6 h), blast thawing (75, 105, 135 min), and cold temperature (18, 21, 24 h). The observations included drip loss, total plate count (TPC), total free fatty acids (FFA), and soluble protein content. The effect of thawing on steamed meat quality was evaluated for the texture, protein content, fat content, and hedonic scores. The data were statistically analyzed using one-way ANOVA test continued by independent sample t-test. The results showed that thawing duration within the same method did not significantly affect drip loss or TPC, but longer thawing times increased FFA across all methods. Prolonged thawing at room and cold temperature significantly reduced soluble protein content. Thawing at cold temperature for 18 h was the most effective with the lowest drip loss (1.12%) and the highest soluble protein content (34.4 mg/g). Results of steamed meat analysis showed significant differences in texture and fat content between thawed and fresh meat, but no significant differences was observed in protein content or hedonic scores